Message in a bottle the making of fetal alcohol syndrome - Golden, Janet 1951- (Harvard University Press, 2006)
This book raises key questions about public policy, the politicization of medical diagnosis, and the persistent failure to address the treatment needs of pregnant alcoholic women. The author traces the history of FAS from a medical problem to moral judgment that stigmatizes certain mothers but falls to extend to them the services that might actually reduce the incidence of this diagnosis.